Mitotic Golgi fragments in HeLa cells and their role in the reassembly pathway (The Rockefeller University Press, 1989)
Immunoelectron microscopy and stereology were used to identify and quantitate Golgi fragments in metaphase HeLa cells and to study Golgi reassembly during telophase. On ultrathin frozen sections of metaphase cells, labeling for the Golgi marker protein, galactosyltransferase, was found over multivesicular Golgi clusters and free vesicles that were found mainly in the mitotic spindle region. The density of Golgi cluster membrane varied from cell to cell and was inversely related to the density of free vesicles in the spindle. There were thousands of free Golgi vesicles and they comprised a significant proportion of the total Golgi membrane. During telophase, the distribution of galactosyltransferase labeling shifted from free Golgi vesicles towards Golgi clusters and the population of free vesicles was depleted. The number of clusters was no more than in metaphase cells so the observed fourfold increase in membrane surface meant that individual clusters had increased in size. More than half of these had cisterna(e) and were located next to "buds" on the endoplasmic reticulum. Early in G1 the number of clusters dropped as they congregated in the juxtanuclear region and fused. These results show that fragmentation of the Golgi apparatus yields Golgi clusters and free vesicles and reassembly from these fragments is at least a two-step process: (a) growth of a limited number of dispersed clusters by accretion and fusion of vesicles to form cisternal clusters next to membranous "buds" on the endoplasmic reticulum; (b) congregation and fusion to form the interphase Golgi stack in the juxtanuclear region.